Analisis Kerentanan Bangunan terhadap Bencana Angin Puting Beliung di Kecamatan TanonKabupaten Sragen - Putra, Kusuma Prayoga Basuki, Drs. Yuli Priyana, M.Si, Dra. Retno Woro Kaeksi (2015)
Tornado is one disaster that can harm even casualties. Tanon Subdistrict Sragen is one of the areas once hit by a tornado. Purpose of this study include: (1). Knowing the wind speed zone by using the Fujita scale prediction of building damage due to the brunt tornado (winds) in District Tanon, (2). Knowing agihan building vulnerability to cyclones in District Tanon, (3). Analyze the vulnerability of buildings to wind velocity zone in District Tanon and (4). Analyze the vulnerability of buildings to damage buildings that have occurred due to the brunt tornado in District Tanon. The method used in the form of a survey using primary data includes observation, recording and retrieval of sample points, and using secondary data as information tornado disaster scene. Sampling was systematic sampling method to determine the vulnerability of buildings and purposive sampling to look for damage to the building and using the analysis in the form of an overlay map. The results include (1). There are 5 zones of wind speed based on the Fujita scale zone of 64-116 km / hour until the zone 33-419 km / hour. (2). Distribution of the vulnerability of buildings scattered and on research areas including medium-high zone of vulnerability and vulnerability analysis buildings against wind speed zones and vulnerability analysis buildings against damage to buildings. Keywords: Building Vulnerability and Zones Wind Speed